THE CONTROVERSY OF MILK BANKS: PERSPECTIVES OF YUSUF AL-QARADAWI AND WAHBAH AZ-ZUHAILI - Nugroho, Nasywa Nabilah; Irham, Muhammad Iqbal; Syahnan, Mhd. (Program Pascasarjana UIN Sumatera Utara, 2025)
This study analyzes the legal status of Breast Milk Banking (ASI) from an Islamic perspective by highlighting the differences in legal approaches between Wahbah az-Zuhaili and Yusuf al-Qaradawi, a theme that still leaves a research gap regarding the limits of radha'ah and the implications of lineage in a modern context. This study uses a library research method with a descriptive-analytical approach through a review of classical and contemporary works, fatwas of scholars, and relevant modern fiqh literature. Data are analyzed through source triangulation and an assessment of the consistency of legal arguments to identify the patterns of ijtihad of the two scholars on the issue of non-direct breastfeeding. The results show that Wahbah az-Zuhaili rejects the practice of Breast Milk Banking due to the potential for mixing lineages and the unclear mahram relationship, considering any form of breast milk entering the baby's body, whether directly or through media, as breastfeeding that has legal consequences. In contrast, Yusuf al-Qaradawi argues that Breast Milk Banking is permissible based on the principle of benefit, because breastfeeding that is not done through direct sucking does not create a mahram relationship. This comparison demonstrates differences in ijtihad methodology: Zuhaili's approach to protecting lineage stems from a precautionary approach, while al-Qaradawi emphasizes the flexibility of Islamic law in addressing contemporary social needs. This study confirms that the legal debate regarding breast milk banking is not only related to technical fiqh issues, but also concerns the methodology of legal istinbath in addressing new phenomena. These findings contribute to the development of contemporary fiqh studies and provide a basis for formulating policies that consider aspects of benefit, infant safety, and clarity of lineage.